UNGKAPAN KEMARAHAN ORANG AMERIKA (STUDI KASUS DALAM FILM A RAISIN IN THE SUN DAN THE HELP) - , Siska Anggraeni ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research entitles Americanâs Anger Expression (A Case Study in A Raisin in the Sun and The Help). Those two films were chosen because they represent the society in the United States in 1960s. This research is based on the three aims to be achieved. First, to describe the forms of anger expression used in A Raisin in the Sun and The Help. Second, to describe the expression of anger expression used in those two films. Third, to define the social factors influencing the anger expression in those films. The form of research is qualitative descriptive. The data are collected by using observation method also recording and note-taking technique. In analyzing the data, this research used the related theory using contextual method. Finally, the findings of analysis are reported in descriptive method. Based on the observations and data analysis, the results of this research are as follows. First, anger expression used in those films appeared in four types of sentences, imperative, declarative, interrogative and exclamatory. Moreover, all of the anger expression is in literal form. Second, the expression of anger can be (1) insulting, (2) commanding, (3) threatening, (4) expressing annoyance (5) denying something, (6) prohibiting (7) challenging (8) accusing and (9) asserting. The last, the social factors proposed by Hymes (1974) are very influencing on the appearance of anger expression. Those factors are setting, participant, ends, key and social norms. In the future, this research can be developed further, especially about the anger expression of American in the present time. The difference of time, norms and social condition will differentiate the research findings.